Shape memory polymer surfaces with controllable roughness for multiscale switchable dry adhesion - Junhyung Kim; Seungbeom Kim; Taehyun Yun; Jeong Hyeon Kim; ChangHee Son; Yongseok Lee; Keehoon Kim; Han Eol Lee; Namjung Kim; Seok Kim (Nature Communications)
Abstract Switchable control of adhesion is an important feature of many desired applications such as robotic manipulation, medical adhesives, and scalable microassembly. We present the study of the switchable dry adhesion of a shape memory polymer surface comprising nanotips which is based on not only overcoming but also exploiting the adhesion paradox, i.e., controlling surface roughness via the shape memory effect. Here, densely packed sharp nanotips causing an initial high surface roughness are flattened upon heating, pressing and cooling to provide a low surface roughness leading to a strong adhesion. However, the flattened nanotips restore their original shape upon reheating to cause a high surface roughness back resulting in a weak adhesion with the adhesion switchability of more than three orders of magnitude. These switchable adhesion capabilities are demonstrated in a variety of applications ranging from macro-scale robotic pick-and-place and fabric adhesives to deterministic micro-scale device-grade silicon platelet transfer and microLED assembly.